Analisis Keterkaitan Capital Flight dan Cadangan Devisa : Pendekatan Vector Error Correction Model (VECM) di Indonesia - Amiroh Amiroh; Maitsaa Zalfaa; Nadila Nadila; Cep Jandi Anwar; Indra Suhendra (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
This study examines the relationship and response to shocks between capital flight and foreign exchange reserves in Indonesia for the 2018-2022 period. This study uses VECM (Vector Error Correction Model) model analysis, aimed at seeing the relationship between capital flight and foreign debt variables and trade balance to Indonesia's foreign exchange reserves. The results of the analysis that have been carried out show that the variable of foreign debt does not affect and is irrelevant to Indonesia's foreign exchange reserves in the long and short term. Meanwhile, trade balance variables affect and are relevant to Indonesia's foreign exchange reserves in the long and short term.